An Intersubjective Analysis of Engineering Leadership Across Organizational Locations: Implications for Higher Education - Rottmann, Cindy; Reeve, Douglas W.; Sacks, Robin; Klassen, Mike (Canadian Journal of Higher Education, 2017)
Engineering leadership education has become increasingly popular over the past decade in response to national calls for educational change. Despite the growing popularity of the movement, however, reform efforts continue to be piecemeal in their delivery, driven largely by the priorities of program leaders who established them (Graham, 2012). If we as engineering educators wish to more systematically develop leadership skills in our students, we should begin by empirically examining and defining our phenomenon of interest: engineering leadership. Our article takes up this challenge by investigating how 82 engineers in five organizationally distinct roles define leadership and how their respective insights are shaped by their diverse organizational locations. After weaving together the perspectives of engineers in industry, human resource professionals, entrepreneurs, politicians and interns, we propose a poly-vocal definition of engineering leadership and identify practical implications for engineering leadership educators.